Examining the Impact of Sexual Revictimization in a Sample of Veterans Undergoing Intensive PTSD Treatment. Issue 23 (December 2021) - Tirone, Vanessa; Smith, Dale; Steigerwald, Victoria L.; Bagley, Jenna M.; Brennan, Michael; Van Horn, Rebecca; Pollack, Mark; Held, Philip
Sexual revictimization refers to exposure to more than one incident of rape and is a known risk factor for poor mental health among civilians. This construct has been understudied among veterans. In addition, although individuals who have experienced revictimization generally have greater symptom severity than those who have experienced one rape, it is unclear whether these differences persist following treatment. This study examined differences between veterans who reported histories of revictimization ( n =111) or a single rape ( n = 45), over the course of a 3-week intensive cognitive processing therapy (CPT)-based treatment program for veterans with posttraumatic stress disorder (PTSD). The sample consisted of predominately female (70.5%) post–9/11 veterans (82.7%). Self-reported PTSD and depression symptom severity were assessed regularly throughout the course of treatment. Controlling for non-interpersonal trauma exposure and whether veterans were seeking treatment for combat or military sexual trauma, sexual revictimization was generally associated with greater pretreatment distress and impairment. However, sexual revictimization did not impact rates of PTSD or depression symptom change over the course of intensive treatment, or overall improvement in these symptoms posttreatment. Our findings suggest that the rates of sexual revictimization are high among treatment-seeking veterans with PTSD. Although veteran survivors of sexual revictimization tend to enter treatment with higher levels of distress and impairment than their singly victimized peers, they are equally as likely to benefit from treatment.